Analysis of Hydroxyproline in Femur of Common Toad for Alteration in Collagen Content by Triiodothyronine - Sahu, Sulata Kumari (International Journal of Scientific Research in Biological Sciences, 2020)
Strength and flexibility of bone came from collagen fibres having crosslinkings. Thyroid hormones have wide scope of impacts on bone tissue. For deciding the nature of bone framework, thyroid hormones are crucial, yet how it is indistinct. Prior examinations recommend that, T3 controls collagen articulation which is portion subordinate and has additionally consequences for collagen crosslinkings. Hypothyroidism causes impaired bone formation and growth retardation where as hyperthyroidism may halt the synthesis of collagen and decreased bone mass. Hydroxyproline and hydroxyllysine are essential for the collagen cross linking and strength of the bone. Examination of hydroxyproline status can be considered as an index of collagen metabolism. As common toad(Duttaphyrnus melanostictus) is studied extensively to gain an elementary knowledge on the anatomy of vertebrates, the above species was used as the experimental organism. The hydroxyproline contents in the femur bone of the experimental and controlled samples were calculated by using Neuman and Logan (1950) method modified by Leach (1960) and values were converted to collagen contents by multiplying with the factor 7.46 as suggested by Jackson and Cleary (1967).From the above values the total collagen content and solubility % were calculated in both control and experimental groups at two different doses of Triiodothyronin(2.0µg/gm&0.5µg/gm). There was no significant outcomes but the % of solubility and ratio of soluble to insoluble has increased insignificantly more at 2.0µg/gm.